2017
DOI: 10.14744/nci.2017.80774
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis following infrarenal abdominal aortic aneurysm treatment: Results from a tertiary medical center

Abstract: OBJECTIVE:The aim of this study was to investigate the effects of ruptured aneurysm on morbidity and mortality in patients with ischemic colitis (IC) and resection following infrarenal abdominal aortic aneurysms (AAA) surgery.METHODS:Between January 2012 and December 2016, patients who underwent resection for ischemic colitis in our clinic were retrospectively reviewed. Data on the ruptured condition of the aneurysm, the emergency or elective form of aneurysm surgery, treatment method for the aneurysm (EVAR-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Thrombophilia due to coagulopathy further increases the 28%-74% risk of ischemic colitis [ 15 ]. Recent research reveals the role of abdominal aortic aneurysm surgery in aggravating ischemic colitis and increasing its mortality rate [ 28 ]. The conditions, including paroxysmal nocturnal hemoglobinuria, protein S/C deficiency, polycythemia vera, and anti-thrombin deficiency, also increase the risk and incidence of ischemic colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombophilia due to coagulopathy further increases the 28%-74% risk of ischemic colitis [ 15 ]. Recent research reveals the role of abdominal aortic aneurysm surgery in aggravating ischemic colitis and increasing its mortality rate [ 28 ]. The conditions, including paroxysmal nocturnal hemoglobinuria, protein S/C deficiency, polycythemia vera, and anti-thrombin deficiency, also increase the risk and incidence of ischemic colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The colonic resection was adapted to the IC extension, leading to a great majority of subtotal or total colectomies. Previous studies reported high mortality rates for IC developed after ruptured AAA repair surgery [15,16,20,26,40], with some differences related to the type of aortic surgery [14,22,40]. Indeed, a recent systematic review and metaanalysis demonstrated that IC occurs more frequently after open repair (2.1-3.6%) than in EVAR (0.5-1%) in the elective setting [22].…”
Section: Discussionmentioning
confidence: 99%
“…Older age, female gender, ruptured aneurysm, emergency surgery, prolonged surgery, aortic clamping duration, and previous cardiovascular history were associated with an increased risk of IC [5,15,17,20,21]. On the contrary, EVAR surgery was found to be protective towards IC compared to open aortic surgery probably due to lower ischemia-reperfusion injury and peripheral proinflammatory cytokine release [16,22,23].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cross-clamping of the aorta, prolonged hypotension, microembolization, colonic trauma during open repair, and reperfusion injury are some of the possible etiologies for the presenting complication. Reduction in perfusion of the inferior mesenteric artery (IMA) can produce ischemia, most commonly on the splenic flexure and rectosigmoid junction due to frail anastomoses between the blood vessels [ 3 ]. Consequently, it can produce life-threatening sequela and contribute to prolonged length of intensive care unit (ICU) stays and accentuate healthcare costs.…”
Section: Introductionmentioning
confidence: 99%